2021
DOI: 10.1002/mame.202100337
|View full text |Cite
|
Sign up to set email alerts
|

Approaches toward High Resilience Rubber Foams: Morphology–Mechanics–Thermodynamics Relationships

Abstract: Natural rubber foam (NRF) products are frequently required in high resilience or high shape recoverability applications, which is in contrast to the fundamental nature of NRF. This study aims to improve NRF properties, such as recovery, by increasing the amount of vulcanizing chemicals (Vc) and adding cassava starch (Cs). Interestingly, increasing the amount of Vc and Cs improves mechanical properties and shape recoverability of NRF although the morphology of NRF with various concentrations of Cs is similar. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…NRF possessed better compression strength and shape recoverability with increasing cassava content and showed the optimum properties at 8 phr. This NRF was intended for high resilience or high shape recoverability applications [37]. After an extensive review, no previous report on NR/rice starch foam used in food packaging applications was found by the authors of this current study.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…NRF possessed better compression strength and shape recoverability with increasing cassava content and showed the optimum properties at 8 phr. This NRF was intended for high resilience or high shape recoverability applications [37]. After an extensive review, no previous report on NR/rice starch foam used in food packaging applications was found by the authors of this current study.…”
Section: Introductionmentioning
confidence: 89%
“…However, these studies have one thing in common: either starch was used as the primary matrix, or the foams were prepared using dry NR under compression moulding. The only study that reported on the production of NR foam as the primary polymer matrix in biocomposites using NR latex as a starting material for foam preparation was by Prasopdee et al [37], in which the cassava starch served as a light filler to improve the recovery properties of natural rubber foam (NRF) prepared through the Dunlop process. Cassava content was varied from 0 to 16 phr.…”
Section: Introductionmentioning
confidence: 99%